2020
DOI: 10.1007/s00190-020-01364-w
|View full text |Cite
|
Sign up to set email alerts
|

BDS-3 differential code bias estimation with undifferenced uncombined model based on triple-frequency observation

Abstract: Since 2015, the new generation global BDS system, i.e., BDS-3, has started its development with five experimental satellites demonstration system and has announced its initial global service officially on December 27, 2018. Among the various characteristics to be analyzed for the new generation BDS satellites, the differential code bias (DCB) is of special attention since that it has a direct dependence on the new signals, i.e., B1C and B2a, and it is one of the most intricacy problems in the ionosphere sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…It should be noted that the receiver biases are absorbed by the ionospheric delay to remove the rank deficiency, thus special attention should be given to the SID modeling for inconsistent receiver networks. Shi et al (2012b) and Zhao et al (2018) presented a sophisticated ionospheric parameter constrain model, i.e., DEterministic plus Stochastic Ionosphere models for GNSS (DESIGN), and it was demonstrated that the ionospheric delay can be separated from the receiver biases in this case (Gu et al 2020;Zhang et al 2021). Typically, the SID modeling performs much better than that of GIM since it uses the LOS ionospheric delay in modelling directly, thus avoiding the errors induced by the elevation mapping function and the constant-height thin-layer model .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the receiver biases are absorbed by the ionospheric delay to remove the rank deficiency, thus special attention should be given to the SID modeling for inconsistent receiver networks. Shi et al (2012b) and Zhao et al (2018) presented a sophisticated ionospheric parameter constrain model, i.e., DEterministic plus Stochastic Ionosphere models for GNSS (DESIGN), and it was demonstrated that the ionospheric delay can be separated from the receiver biases in this case (Gu et al 2020;Zhang et al 2021). Typically, the SID modeling performs much better than that of GIM since it uses the LOS ionospheric delay in modelling directly, thus avoiding the errors induced by the elevation mapping function and the constant-height thin-layer model .…”
Section: Introductionmentioning
confidence: 99%
“…From the above discussion, it is concluded that the uncombined model provides a better way to realize an overall estimation of both satellite PIFCB and CIFCB which are consistent with the IGS clocks. However, the uncombined model for IFCB or DCB estimation and correction was merely validated by triple-frequency data in previous studies (Guo and Geng 2017;Liu et al 2018;Pan et al 2018a, b;Fan et al 2019;Gu et al 2020). When data on more than three frequencies are considered, numerous IFCBs that can be formed from any three frequencies are not unified in the uncombined model.…”
Section: Introductionmentioning
confidence: 99%
“…BDS-3 retains B1I and B3I of BDS-2 to realise the transition from BDS-2 to BDS-3. On this basis, BDS-3 also transmits three new frequency signals to achieve compatibility and interoperability with other GNSSs, namely, B1C at 1575.42 MHz, B2a at 1176.45 MHz, and B2b at 1207.14 MHz (CSNO 2019aGu et al 2020).…”
Section: Introductionmentioning
confidence: 99%